Emerging Opportunities Provided by Technology to Advance Research in Child Health Globally. (May 2020) - van Heerden, Alastair; Leppanen, Jukka; Rotheram-Borus, Mary Jane; Worthman, Carol M.; Kohrt, Brandon A.; Skeen, Sarah; Giese, Sonja; Hughes, Rob; Bohmer, Lisa; Tomlinson, Mark
Current approaches to longitudinal assessment of children's developmental and psychological well-being, as mandated in the United Nations Sustainable Development Goals, are expensive and time consuming. Substantive understanding of global progress toward these goals will require a suite of new robust, cost-effective research tools designed to assess key developmental processes in diverse settings. While first steps have been taken toward this end through efforts such as the National Institutes of Health's Toolbox, experience-near approaches including naturalistic observation have remained too costly and time consuming to scale to the population level. This perspective presents 4 emerging technologies with high potential for advancing the field of child health and development research, namely (1) affective computing, (2) ubiquitous computing, (3) eye tracking, and (4) machine learning. By drawing attention of scientists, policy makers, investors/funders, and the media to the applications and potential risks of these emerging opportunities, we hope to inspire a fresh wave of innovation and new solutions to the global challenges faced by children and their families.